Pelatihan ketrampilan servis kulkas di Panti Asuhan Putera Muhammadiyah Cabang Medan Kota - Mukhtar, Muharnif; Suherman; Rahmatullah; Khair, Hadriman (LPPM Universitas Al-Azhar medan, 2025)
Orphanages as Child Welfare Institutions have a very important role in improving children's education, especially life skills as provisions for facing competition in the world of work. The lack of life skills training received by Muhammadiyah Orphanage children due to limited funds is one of the reasons for providing refrigerator service skills training to orphanage children. The choice of refrigerator service training is because almost every household has a refrigerator for storing food and drinks so that they last a long time. This is certainly a market share that is quite promising in providing refrigerator service services. The aim of this program is to provide life skills to orphanage children so that they have the ability to work and become entrepreneurs in providing refrigerator servicing and become a source of income for the orphanage. This method is implemented by providing direct training in the form of theory and practice with training material consisting of refrigerator working mechanisms, introduction and use of the equipment used, and refrigerator repair practices including measuring pressure and electric current, cutting and welding copper pipes, vacuuming and filling refrigerant. as well as compressor replacement. The results obtained by training participants are understanding the working mechanism and the ability to detect damage and repair the refrigerator.